2021
DOI: 10.1038/s41598-021-96804-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mortality and survival in multiple myeloma compared to other hematopoietic neoplasms in Sweden up to year 2016

Abstract: Survival in multiple myeloma (MM) has developed favorably over the past decades for reasons that have been ascribed to new medications and treatment. However, development of survival over a long period and comparison to other hematopoietic neoplasms (HN) is less well known. Here we used Swedish cancer data from the Nordcan database, spanning a 50-year period from 1967 to 2016, and analyzed 1- and 5-year survival data. As a novel type of analysis we calculate the difference in survival between year 1 and 5 whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…With the in-depth exploration of the pathogenesis and drug development of MM, many therapies, such as proteasome inhibitors, immunomodulatory drugs, antibody-drug conjugates (ADC) and chimeric antigen receptor (CAR) T-cell therapy, have been applied to MM, and achieved certain curative effects [ 5 ]. These drugs alone or in combination can improve the survival rate of newly diagnosed or relapsed MM patients from 25% in the mid-1970s to 55% [ 6 ]. The recent follow-up results of a phase III clinical trial for relapsed/refractory (RR) MM patients showed that patients treated with caffezomib, dyramuzumab and dexamethasone (KdD) had a higher realization rate of minimal residual disease-negative (MRD-) than patients treated with caffezomib and dexamethasone (Kd) (28% vs 9%), and the median PFS and OS of KdD group were significantly higher than those of Kd group [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the in-depth exploration of the pathogenesis and drug development of MM, many therapies, such as proteasome inhibitors, immunomodulatory drugs, antibody-drug conjugates (ADC) and chimeric antigen receptor (CAR) T-cell therapy, have been applied to MM, and achieved certain curative effects [ 5 ]. These drugs alone or in combination can improve the survival rate of newly diagnosed or relapsed MM patients from 25% in the mid-1970s to 55% [ 6 ]. The recent follow-up results of a phase III clinical trial for relapsed/refractory (RR) MM patients showed that patients treated with caffezomib, dyramuzumab and dexamethasone (KdD) had a higher realization rate of minimal residual disease-negative (MRD-) than patients treated with caffezomib and dexamethasone (Kd) (28% vs 9%), and the median PFS and OS of KdD group were significantly higher than those of Kd group [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Nordic cancer registries are a powerful resource as they are the oldest cancer registries in the world and have almost complete case ascertainment, allowing for the study of cancer survival over 50 years with minimization of bias introduced through ascertainment [9]. Grouped data from these registries are accessible as the NORDCAN database, which has been the source of numerous survival studies, including those on HMs starting from the 1960s [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…After Northern Europe, Australia follows with a rate of 5.6, the US with 5.5, and Canada with an incidence of 5.3 per 100,000, respectively. In South America, the highest [8,9] incidence is estimated to be found in Mexico, at 2.7 cases per 100,000 person-years [15]. Moreover, about 180,000 deaths from primary brain tumors are recorded annually in the world, which is 2.03% of all cancer deaths.…”
Section: Introductionmentioning
confidence: 99%